VD_FINDINFO Décision / 2013 / 165 vom 14. April 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, VIOLATION DU SECRET PROFESSIONNELDROIT PÉNAL | 321 ch. 1 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)